Температурная зависимость микротвердости композитов на основе алмазного нанопорошка детонационного синтеза - Бочечка, А.А.; Шульженко, А.А.; Александрова, Л.И.; Гаврилова, В.С.; Заика, Н.И.; Лошак, М.Г.; Назарчук, С.Н.; Романко, Л.А. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2007)
Results of studying of hardness, fracture toughness and temperature dependence of microhardness of composites based on diamond nanopowder of detonation synthesis UDD and carbides of transitive metals, and also, polycrystals sintered from diamond nanopowder of static synthesis are considered. It is shown, that composite UDD–WC has the highest level of physicomechanical properties.